Consumers' responses to CSR in a cross-cultural setting - Hakan Karaosman; Gustavo Morales-Alonso; Mercedes Grijalvo; Collins Gyakari Ntim (Cogent Business & Management, 2015)
The paper aims to clarify the relationship between corporate social responsibility (CSR) and consumer behaviour in an international setting. Consumers' responses to CSR activities and the impact on the purchase decision are limited discourses. CSR-based studies in the fashion and apparel industry are also scarce. Therefore, this study attempts to enlighten the subject of how consumers from different countries respond to CSR adopted in the fashion and apparel industry. This study is based on an exploratory qualitative research for which focus group interviews, including six group discussions with Spanish and Turkish consumers, have been used. The fundamental dimension for sampling was consumers' interest and knowledge of CSR-related issues. The data were examined by constant comparison analysis. The paper provides empirical insights that suggest that these consumers, regardless of their country of origin, perceive CSR actions as part of companies' marketing strategies, while overall consumer awareness to CSR is low. Moreover, the criteria, which determine the purchase decision is to be governed by self-interest. A difference between participants from both countries has been found with regard to their demand for more regulation towards CSR. An identified research need in international marketing discipline, is fulfilled in this study.
Keywords: 650